Tourists’ Perception towards Cox’s Bazar Sea Beach in Bangladesh as a Tourist Destination - Dey, Prodip; Uddin, Shamsu; Hasan, Md. Kamrul (Asian Business Review, 2013)
The study was carried out on Cox’s Bazar sea beach area, the world longest sea beach and the tourist capital of Bangladesh. The purpose of the present study is to investigate the tourists’ perception towards various facilities and services at Cox’s Bazar sea beach as a tourists’ destination. The study was based on primary as well as secondary data; applied quantitative method and 308 questionnaires were used. The factor analysis was conducted to create correlated variable composites from the original attributes. The results of the study stated that tourists’ perception is favorable on  Factor 1, Natural Beauty and Restful Atmosphere, Factor 3, Accommodation and security, Factor 4, Hospitality and information and Factor 6, Shopping and activities and tourists’ perception is unfavorable on Factor 2, Hygiene and Sanitation  and Factor 5, emergency and caring services. The findings of the current research suggest that there are statistically significant differences in tourists’ perception with respects of respondents’ demographic characteristics such as respondents’ gender, age, occupation and education in some services and facilities at Cox’s Bazar. The findings suggest that the tourism market players, managers and policy makers should ensure up to the mark services with unfavorable factors and differentiated marketing strategies should be stressed and executed by the relevant parties. Therefore, the findings of the study also provided theoretical and practical implications for the planners, marketers and tourism authorities of Cox’s Bazaar in formulating strategies to maintain or enhance their competitiveness.JEL Classification Code:  M31
Keywords: Beach tourism; Tourists’ perception; Natural beauty; Hygiene and Sanitation facility; Factor Analysis; Cox’s Bazar Sea beach